Profil fraktur diafisis femur periode Januari 2013 – Desember 2014 di RSUP Prof. Dr. R. D. Kandou Manado - Wattie, Ezra A. W.; Monoarfa, Alwin; Limpeleh, Hilman P. (Universitas Sam Ratulangi, 2016)
Abstract: The incidence of femoral diaphysis fracture has increased recently. The most common cause of this fracture is motor vehicle accident. Femoral diaphysis fracture can be accompanied by multiple fractures (fractures of other bones) which depends on the cause. This study aimed to determine the distribution of the femoral diaphysis fracture cases by age, gender, anatomical location of the fracture, type of fracture (open and closed), and the management (adults and children). This was a descriptive retrospective study. Samples were all patients with femoral diaphysis fractures treated in the period of January 2013 to December 2014. Data of the patients were obtained from the medical records of Surgery Department based on the variables. The age was categoried of: children (0-11), teenagers (12-17), young adults (18-44), older adults (45-64), and elderly (65+). The anatomical location of the fracture consisted of 1/3 proximal, 1/3 medial, and 1/3 distal. The management of adult patients were ORIF (plate and screw), ORIF (screw and wiring), and ORIF (Kuntscher nail). The management of children was Hamilton-Russell traction, Bryan traction, and distal skeletal traction. The results showed that there were 45 patients in the 2-year period consisting of 29 (64.5%) patients in 2013 and 16 (35.5%) patients in 2014. The gender which dominated these cases was male with 26 patients (57.8%). Females were only 10 patients (22.2%). There were 9 patients (20.0%) without ae and sex categories. Among males, the fracture occurred in children (2 patients, 4.4%), adolescents (8 patients, 21.7%), young adults (10 patients, 22.2%), older adults (5 patients, 11.1%), and the elderly (1 patient, 2.2%) The incidence in women increased in older adults (5 patients, 11.1%). According to the anatomic location of the fracture, the highest incidence was in the 1/3 medial of the femoral diaphysis (30 patients, 66.6%). The most common type of fracture based on the exposure to the external environment is closed fractures (27 patients, 60%). The distribution of the cases based on the operative management of adult patients did not provide any meaningful information because there had been a lot of patients (31 patients, 68.8% of the existing data) that did not include the type of operative management. The case distribution based on the treatment of children showed no traction. Conclusion: There was an increase of the femoral diaphysis cases which was more significant in males than in females with the growing incidence in young adult males. While in women, there was a slight increase in the incidence in older adults. Keywords: femoral diaphysis fracture Abstrak: Angka kejadian meningkat pada fraktur diafisis femur dengan penyebab tersering kecelakaan kendaraan bermotor. Fraktur diafisis femur bisa disertai dengan fraktur multipel (fraktur pada tulang-tulang yang lain) tergantung dengan penyebabnya. Penelitian ini bertujuan untuk mengetahui distribusi kasus fraktur diafisis femur berdasarkan umur, jenis kelamin, lokasi anatomis fraktur, jenis fraktur (terbuka dan tertutup), dan penatalaksanaan (dewasa dan anak-anak). Jenis penelitian ini deskriptif retrospektif. Sampel ialah semua pasien fraktur diafisis femur yang dirawat pada periode Januari 2013 – Desember 2014. Data pasien diambil dari PPDS Ilmu Bedah berdasarkan variabel-variabel yang akan diteliti. Umur yaitu berdasarkan kategori anak-anak (0-11), remaja (12-17), dewasa muda (18-44), dewasa tua (45-64), dan lanjut usia (65+). Lokasi anatomis fraktur yaitu terdiri dari 1/3 proximal, 1/3 medial, dan 1/3 distal. Penatalaksanaan pada pasien dewasa yaitu ORIF (plate & screw), ORIF (screw & wiring), dan ORIF (Kuntscher nail). Tatalaksana pada anak-anak yaitu traksi Hamilton-Russel, traksi Bryant, dan traksi skeletal distal. Hasil penbelitian memperlihatkan terdapat 45 Pasien dalam periode 2 tahun: 29 (64,5%) pasien pada tahun 2013 dan 16 (35,5%) pasien pada tahun 2014. Jenis kelamin yang mendominasi kasus ialah laki-laki yaitu 26 pasien (57,8% dari keseluruhan data). Pada perempuan diperoleh 10 pasien (22,2% dari keseluruhan data). Terdapat 9 pasien (20,0%) yang tidak tercantum umur dan jenis kelamin. Pada laki-laki, fraktur ditemukan pada: anak-anak (2 pasien, 4,4%), remaja (8 pasien, 21,7%), dewasa muda (10 pasien, 22,2%), dewasa tua (5 pasien, 11,1%), dan usia lanjut (1 pasien, 2.2%). Angka kejadian pada perempuan meningkat pada kategori usia dewasa tua (5 pasien, 11,1%). Pada distribusi pasien menurut lokasi anatomis fraktur, insiden tertinggi pada lokasi 1/3 medial diafisis femur (30 pasien, 66.6%). Jenis fraktur tersering berdasarkan ada atau tidaknya paparan lingkungan eksternal ialah fraktur tertutup (27 pasien, 60%). Distribusi kasus berdasarkan tatalaksana operatif pada pasien dewasa tidak memberikan info yang bermakna oleh karena terdapat banyak pasien (31 pasien, 68,8%) yang tidak mencantumkan jenis tatalaksana operatif. Pada distribusi kasus berdasarkan tatalaksana pada anak-anak tidak ditemukan pasien yang menjalani traksi. Simpulan: Terdapat peningkatan kasus fraktur diafisis femur yang bermakna pada laki-laki dibanding perempuan dengan insiden meningkat pada laki-laki dewasa muda. Pada perempuan, terjadi sedikit peningkatan insiden pada usia dewasa tua. Kata kunci: fraktur diafisis femur